Peningkatan Proses Pembelajaran Tematik dengan Model Kooperatif Tipe Tgt di Kelas III SD Negeri 18 Langgini Bangkinang - Putri Hana Pebriana (Jurnal Basicedu, 2017)
This research was conducted as the thematic learning process in class III of SD Negeri 18 Langgini Bangkinang was not run as it was expected. This made the students' social skill was not developedmaximally. Therefore, this research sought to improve the thematic learning processby using TGT cooperative learning model.This was a Classroom Action Research which was conducted in two cycles inwhich each cycle consisted of four phases covering planning, acting, observing andreflecting. The subject of the research was the teacher and 33 students; 17 malestudents and 16 female students. The data was collected through observation.The results of the research disclosed that the use of TGT cooperative learning modelcould improve the thqatic learning process in class III of SD Negeri 18 Langgini Bangkinang. In the first cycle, ingroup works, the students' score in tolerance attitude was 52,98, their activeness towork in group was 59,33, their ability to present their work was 56,07, and theircourage to express ideas was 57,08. Meanwhile their average score in Indonesian was5,29, in Social Science was 7,53, in Natural Science was 6,21 and in Mathematicswas 7,19, or in general their average score was less than adequate.In the second cycle, their score in tolerance attitude was 85,59, theiractiveness to work in group was 85,95; their ability to present their work was 87,41,and their courage to express ideps was 86,64. Meanwhile their average score inlndonesian was 8,01, in Social Science was 8,02, in Nafural Science was 8,79 and inMathematics was 9,07, or in general their average score was good.Hence, the thematiq leaming could be improved by using TGT cooperativelearning model. This could be seen from the significant improvement of the thematiclearning process from the first cycle to the second one either in pre-teaching, whilstteachingor post-teaching.